Analyse de la crise financière actuelle - Bernard Vallageas (Revue de la Régulation)
The first stage of the plan for rescuing French banks in October 2008 rules that a special company owned by the State and the banks will borrow on the “markets” with the State warranty. The money collected will be lent to the banks so that they can finance economy. This is curious because there is no explanation of money creation, as if “markets” created money. Actually we demonstrate that the banks can use the special company to create money for themselves, then to lend the money to economy and use the State-warranted bonds as a collateral for refinancing from the European Central Bank. So the State behaves as an insurer allowing to borrow from the European Central Bank.